Finding the spaces between forms: An inquiry into memory work through the intermedial interplay between media and presence - Pilkington, Nicola (Little Theatre, 2024)
This study sought to explicate my intermedial performance praxis as a theatre-maker, filmmaker and researcher. Intermedial performance practice was a generative way to respond to the gathering restrictions as a multidisciplinary artist during the Covid-19 pandemic; and a meaningful method to carry out a self-reflexive autoethnographic study about the frictions between embodied and recorded forms of memory. What emerged was an inquiry into the interplay between media and presence in memory work, which is the “conscious and purposeful staging of memory” as proposed by Kuhn Annette (2000: 186). Through a self-reflexive and responsive practice-as-research approach, I sought to frame and articulate the handling of my intermedial performance practice. I draw on Gayatri Chakravorty Spivak and her notion of planetarity (2003, 2015, 2017) and similarly, Donna Harroway and her motion toward Staying with the Trouble (2016), toward complex networking, alliance, and entanglement; through engagement in worldings and play in order to open up possibilities. Working within a worlding that premised on specificity, multiplicity and plurality, I draw on Walter Mignolo's idea of empowering the utterance as a mode of placing the subjective self in all the work I have generated throughout the course. My formal inquiry into my intermedial performance practice began largely in response to the alienation caused by the global pandemic. I was prompted to interrogate ideas of intimacy and tactility at a time of physical distance. This took the form of an online process with Hlabi Moetanalo and resulted in the output of an interactive zine that unlocks digital performances through QR codes. This investigation gained scope and sought to reflect on how the continued separation effects community. Through an online process with Shameelah Khan and Geoffrey Diver, gathering in the age of digitality was explored through an intermedial performance practice. This resulted in a live-streamed telematic performance (or what I call a Zoomformance), now remediated into an Instagram exhibition. These projects were titled, Hybrid but Human: Vol 1. (2021) and Hybrid but Human: Towards a digital dramaturgy (2021) respectively. As gathering restrictions started to ease, my focus turned to an autoethnographic study into memory work, made in response to the repository of personal family home videos. While autoethnographic performance and autoethnographic filmmaking are well theorised fields (with particular reference to Catherine Russell and Tami Spry), I sought to generate an autoethnographic text through an intermedial performance praxis. I wanted to probe the possibilities, frictions, and fissures between the memories stored in my family's home videos and the memories stored in my body. And thus I created a memory text, an intermedial performance work about my relationship to the stage, screen and utterances of self therein. This resulted in a 20-minute performance titled The Camera & I (2022)